OPTIMALISASI MEDIA GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Mustafa (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2019)
This study aims to improve student learning outcomes through the application of picture media in the learning process at SD Negeri 4 Sigli. This study used the Classroom Action Research (CAR) method. The research subjects were 24 students. Data collection techniques were carried out through tests, observations, and documentation, while the data were analyzed descriptively quantitatively. The results showed that in Cycle I, the average value of student learning outcomes reached 51.5 with a classical completeness of 16.6%, where only 4 of 24 students reached the high category. After learning improvements were made in Cycle II, the average value increased to 81.3 with a classical completeness of 66.7%, and the number of students reaching the high category increased to 16 people. Therefore, it can be concluded that the use of picture media can improve student learning outcomes.